Words, Ideas and Ideology in the Shifting Sand of Markets - Qadeer, Imrana; Arathi P.M. (Indian journal of gender studies, 2016)
The transformation of existing knowledge or production of new knowledge is the focus of this article. This theme is explored using women’s health, actions and perceptions, and their interpretations—within a public health perspective—as these evolve around the currently most talked about high-tech obstetric intervention—the practice of surrogacy. The interpretations of words such as production, reproduction, labour and work are central to the present understanding of surrogacy in different societies. At a point in time when social sciences are striving to understand complexities, interconnections and praxis, this article offers a possibility of judicious use of technology and a glimpse, however brief, of man’s natural essence—humanness—the cementing factor in the alternate structure of society waiting to overcome the present conflict between the global hegemonic and democratic forces. The article argues that in contemporary India, the sections where surrogates come from see surrogacy in different ways, and that has to be the starting point for analysis but not the end. Indian law-makers take advantage of this confusion about the nature of surrogacy. It buries the non-exploitative potential of procreation under the ‘compensation for agreeing’ to be a surrogate, denies her rights and undermines the value of gestational motherhood as compared to genetic identity—thus, killing several birds with one stone!